Retrospective analysis of custom 3D-printed drill guides and titanium plate use in spinal stabilization of eleven dogs - Guirguis, Phillip; Asanovic, Ilja; Beggs, David S.; Long, Sam N. (Frontiers in Veterinary Science, 2024)
IntroductionCongenital vertebral malformations are common developmental abnormalities in screw-tailed brachycephalic dog breeds. Subsequent vertebral instability and/or vertebral canal stenosis caused by these malformations can lead to spinal cord compression manifesting in pain, paraparesis, ataxia and/or paralysis. Various methods for spinal stabilization are in common use. However, these are without significant risk due to narrow margins of surgical error and variable vertebral anatomy. We evaluate a novel method for spinal stabilization where a custom 3D-printed plate is created and surgically fitted to the patient’s spine using custom 3D-printed drill guides.ObjectiveTo describe the surgical technique and short-term outcomes in patients treated with custom 3D-printed plates and drill guides.MethodA retrospective analysis of 11 dogs from two referral hospitals which underwent this procedure was undertaken. Post-operative CT scans were assessed for spinal canal screw perforation using the modified Zdichavsky classification. Pre-operative and post-operative neurological status were assessed using the Modified Frankel Scale and the surgical technique including post-operative imaging and recovery findings were described.ResultsOptimal screw placement (grade I) was achieved in 63% of placed screws across the eleven dogs. Partial penetration of the medial wall (grade IIa) was observed in 3% of screws and partial penetration of the lateral wall (grade IIIa) was observed in 29% of screws. Full penetration of the lateral pedicle wall (grade IIIb) was observed in 5% of screws and no screws fully penetrated the medial vertebral wall (grade IIb).DiscussionWe demonstrated that custom 3D-printed drill guides and titanium plates can provide a safe peri-operative alternative for surgical spinal stabilization of dogs with vertebral column instability due to congenital vertebral malformations. Further research is needed to describe long-term outcomes of this surgical technique on patient health.